A basin scale assessment framework of onshore aquifer-based CO2 suitability storage in Tampico Misantla basin, Mexico. (May 2023) - Medina, Erik; Levresse, Gilles; Carrera-Hernández, Jaime J.; Cerca, Mariano
Highlights: The Tampico Misantla giant oil-producing basin is suitable for CCS. The Tampico Misantla basin has potential to safely store 2128.6 Mt of CO2 in two different aquifer formations. Storage volumes identified point out that CCS can help Mexico to reach the targets set by the Paris Agreement. Even with the most conservative criteria, the Basin scale evaluation involve significant inconsistencies and uncertainties related to technical assumptions and techno-economic and social features. Abstract: The importance of CO2 storage in deep geological formations to mitigate CO2 emissions, has triggered the investigation of possible sites worldwide. This study presents a hierarchical basin-wide evaluation of the Tampico-Misantla basin (TMB), Mexico, following a basin evaluation methodology based on literature criteria and local particularities. The results show that the TMB has significant potential to adequately store CO2 . The stratigraphy evaluation reveals two candidate aquifers: (1) the Cretaceous Tamaulipas and (2) the Jurassic Cahuasas formations. Twenty-three criteria are taken into account to evaluate the storage potential of the area. A numerical scoring and weighting scheme integrate all the criteria in a raster, thus allowing the storage potential to be depicted using a normalized scale. The prospective areas are restricted by the 0.8 isoline normalized value (over 1). Considering the aquifer's volume with potential above 0.8, the effective storage capacity of the basin is estimated to be 972.3 to 1346.0 million tonnes of CO2 .